Dissociation of Golgi-associated DHHC-type Zinc Finger Protein (GODZ)- and Sertoli Cell Gene with a Zinc Finger Domain-β (SERZ-β)-mediated Palmitoylation by Loss of Function Analyses in Knock-out Mice - Kilpatrick, Casey L.; Murakami, Shoko; Feng, Mengyang; Wu, Xia; Lal, Rachnanjali; Chen, Gong; Du, Keyong; Luscher, Bernhard (The Journal of biological chemistry, 2016)
The γ2 subunit of GABA type A receptors (GABAARs) is thought to be subject to palmitoylation by both Golgi-associated DHHC-type zinc finger protein (GODZ; also known as DHHC3) and its paralog Sertoli cell gene with a zinc finger domain-β (SERZ-β; DHHC7) based on overexpression of enzymes and substrates in heterologous cells. Here we have further investigated the substrate specificity of these enzymes by characterization of GODZ and SERZ-β knock-out (KO) mice as well as double KO (DKO) neurons. Palmitoylation of γ2 and a second substrate, growth-associated protein of 43 kDa, that is independently implicated in trafficking of GABAARs was significantly reduced in brain of GODZ KO versus wild-type (WT) mice but unaltered in SERZ-β KO mice. Accumulation of GABAARs at synapses, GABAergic innervation, and synaptic function were reduced in GODZ KO and DKO neurons to a similar extent, indicating that SERZ-β does not contribute to palmitoylation or trafficking of GABAARs even in the absence of GODZ. Notably, these effects were seen only when mutant neurons were grown in competition with WT neurons, thereby mimicking conditions of shRNA-transfected neurons previously used to characterize GODZ. However, GABA-evoked whole-cell currents of DKO neurons and the GABAAR cell surface expression in DKO neurons and GODZ or SERZ-β KO brain slices were unaltered, indicating that GODZ-mediated palmitoylation selectively controls the pool of receptors at synapses. The different substrate specificities of GODZ and SERZ-β in vivo were correlated with their differential localization to cis- versus trans-Golgi compartment, a mechanism that was compromised by overexpression of GODZ.